Hair mercury levels in different occupational groups in Southern Bolivar (Columbia) - Olivero, Jesús; Mendonza, Claudia; Mestre, Judith (Revista de Saúde Pública, 1995)
Hair mercury analysis was carried out on a sample of 219 people living in the main gold mining zone of Colombia, 27 inhabitante of Cartagena City being taken as control sample. For data analysis the sample was divided by occupation and the corresponding the hair mercury concentrations (mean ± SD) were found to be 5.23 ± 5.78, 2.83 ± 3.27, 2.4 ± 2.02 and 1.33 ±0.74 µg/g for fishermen, miners, people of various other activities and the control sample, respectively. According to variance analysis and the Newman Keuls test, there were significant differences (p